Extent of Integration of Information and Communication Technologies in Classroom Instruction in Nepad E-Schools, Kenya - Mogeni, Jackson Mobisa; Ondigi, Prof. Samson R.; Mugo, Dr. Bernard C. (Journal of Education and Practice, 2020)
Purpose: The purpose of this study was to determine the extent to which teachers integrate ICTs in classroom teaching and learning in NEPAD e-Schools, Kenya. Methodology: This study adopted a descriptive survey design and collected quantitative and qualitative data using mixed methods. The target population were 256 teachers. Sampling was done employing a mixture of techniques; stratified sampling to pick 5 schools, and purposive sampling to pick 110 teachers. Data were collected using questionnaire, resources checklist and observation. Data were coded, and run for descriptive analysis; including frequencies, percentages, measures of central tendency and measures of variability using SPSS version 22.0. Data were then presented aided by notes, frequency tables, percentages, charts and figures. Findings: Schools had functional, but unreliable electricity, and had altered ICTs to different degrees and directions; some had either been replaced or totally lost. The schools faced maintenance challenges; impeding ICTs integration in instruction. More teachers infrequently, or rarely integrated ICTs than those who did so regularly. The mean frequency of ICTs integration was once a month. Computers and word processing were teachers' most preferred ICT tools. Teachers mainly used ICTs to illustrate main ideas during lessons. Subject content mostly determined choice and use of instructional ICTs. Most teachers found ICTs integration being generally easy, had above average proficiency in integrating ICTs, and could apply their technological, pedagogical and content knowledge well. The study concludes that teachers are alienated from integrating ICTs frequently owing to their location. Therefore, there is need to designate more places for teachers to be unimpeded from accessing and integrating ICTs. Unique contribution to theory, practice and policy: The study lends insights to other instructional ICTs initiatives to reminisce and study as they initiate or expand their projects; like provision and sustenance of infrastructure, tools, and support services. It also contributes to the body of knowledge in educational technology, which might inform theory and practice in ICTs integration. It could also inform the development of best practices in application and integration of ICTs in instruction.